Farmers’ Perceptions on Soil Degradation and Their Socioeconomic Determinants in Three Watersheds of Southern Benin - KOUELO ALLADASSI, FÉLIX; HOUNGNANDAN, PASCAL; AZONTONDE, ANASTASE; DEDEHOUANOU, HOUINSOU; GANGNON, SEMEVO OSLO ARMEL (My University, 2015)
Soil degradation is one of the most serious ecological and environmental problems in south of Benin. Understanding farmers’ perceptions of soil degradation and its causes is important in promoting soil and water conservation practices. The objective was to examine farmers’ perceptions, understanding and interpretation of soil degradation factors and socioeconomic characteristics that influence these perceptions. A survey was conducted in Allada, Aplahoué and Djidja districts, which had respectively the watersheds of Govié, Lokogba and Linsinlin in southern Benin. The study was based on the data obtained from 427 sample households heads using pre-tested structured interview schedule. The data were analyzed using simple descriptive statistics and frequencies with the chi-square test. The finding of the study shows that almost all farmers of the study area had good perception on the causes, indicators and problems of soil degradation. Farmers explained soil degradation as soil fertility depletion and soil erosion (soil loss). The main causes of soil erosion perceived by farmers were slope, runoff, rain intensity and duration. According to the farmers, the soil fertility depletion is mainly caused by deforestation, bushfires, continuous cropping, soil type and animal trampling. Several socioeconomic characteristics influence significantly the farmers’ perceptions as gender, literacy, agricultural extension and/or membership of farmers’ organization. The farmers’ perceptions vary significantly according to cropping systems, therefore, from village to village, with their socioeconomic determinants.
Keywords: Farmers’ perceptions; soil degradation; soil erosion; soil fertility decline; socioeconomic determinants; southern Benin